Emerging Biomarkers in Atherosclerosis: Advancing Early Detection and Risk Stratification - Sojka, Aleksandra; Sosin, Julia; Pilarz, Anna; Stachowiak, Julia; Zwierzchowska, Maria; Salamon, Dariusz; Domagała, Wojciech (Quality in Sport, 2024)
Introduction: Atherosclerosis is a complex, multifactorial disease influenced by both genetic and environmental factors, including obesity, cigarette smoking, excessive alcohol consumption, and certain chronic conditions such as hypertension and diabetes mellitus type 2. The disease progresses gradually, and often remains unnoticed for years until serious health complications such as coronary artery disease (CAD), peripheral artery disease (PAD) or cerebrovascular disease arise. Nowadays, the diagnosis of atherosclerosis relies on the identification of specific biological markers, enabling early detection and assessment of disease progression. The most common markers used in clinical practice include low-density lipoprotein (LDL), high-density lipoprotein (HDL), triglycerides (TGs), and lipoprotein(a) (Lpa). However, considering that atherosclerosis is one of the leading causes of mortality worldwide and its etiology still remains insufficiently elucidated, there is a pressing need for new, more specific biomarkers for its earlier detection. Aim of the study: The aim of this study is to summarize the knowledge concerning new potential biomarkers for the early detection of atherosclerosis through analyzing the biological processes associated with the initiation and progression of the disease, such as inflammation, oxidative stress, and endothelial dysfunction, to better understand its pathophysiology. Materials and methods: A systematic review of scientific and medical literature from the PubMed and Google Scholar databases was conducted. Results: The analysis of available studies indicates that there are numerous potential biomarkers that might be used for the early diagnosis of atherosclerosis, such as molecules associated with inflammation, lipid oxidation, or endothelial damage. However, further research is needed to establish their full clinical utility.